2013
DOI: 10.1007/s11060-012-1038-6
|View full text |Cite
|
Sign up to set email alerts
|

MEG3: a novel long noncoding potentially tumour-suppressing RNA in meningiomas

Abstract: Meningiomas represent one of the most common types of primary intracranial tumours. However, the specific molecular mechanisms underlying their pathogenesis remain uncertain. Loss of chromosomes 22q, 1p, and 14q have been implicated in most meningiomas. Inactivation of the NF2 gene at 22q12 has been identified as an early event in their pathogenesis, whereas abnormalities of chromosome 14 have been reported in higher-grade as well as recurrent tumours. It has long been supposed that chromosome 14q32 contains a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 69 publications
2
72
0
1
Order By: Relevance
“…We found that two lncRNAs - MEG3 (Maternally Expressed Gene 3) and KIAA0125 - compete for the role of the first hub and regulate the expression of the almost totality of the mRNAs in the cancer-MMI-network, by antagonizing mir-379 and mir-150, respectively (Additional file 5: Tables S5 and S10). Of note, MEG3 was recently suggested to play a significant role as a novel tumor suppressor lncRNA in several human cancers and evidence of its association with tumorigenesis is growing every day [41-43]. Functional annotation enrichment analysis of nodes in this larger sub-network clearly points to immune system-related functions (Additional file 12: Figure S3 and Additional file 13: Table S11).…”
Section: Resultsmentioning
confidence: 96%
“…We found that two lncRNAs - MEG3 (Maternally Expressed Gene 3) and KIAA0125 - compete for the role of the first hub and regulate the expression of the almost totality of the mRNAs in the cancer-MMI-network, by antagonizing mir-379 and mir-150, respectively (Additional file 5: Tables S5 and S10). Of note, MEG3 was recently suggested to play a significant role as a novel tumor suppressor lncRNA in several human cancers and evidence of its association with tumorigenesis is growing every day [41-43]. Functional annotation enrichment analysis of nodes in this larger sub-network clearly points to immune system-related functions (Additional file 12: Figure S3 and Additional file 13: Table S11).…”
Section: Resultsmentioning
confidence: 96%
“…For example, the 21 kb lncRNA MEG3 was up-regulated in fetal heart and is a known tumor suppressor. 27 A second 382 bp lncRNA, BCYRN1, was up-regulated in adult heart and has been reported to be up-regulated and targeted by c-MYC in non-small-cell lung cancer. 28 …”
Section: Resultsmentioning
confidence: 99%
“…Meg3 is an imprinted gene, and its transcript is a noncoding RNA highly expressed in the developing and adult mouse neocortex, hypothalamus, hippocampus, and amygdala (Balik et al, 2013). The human homolog of the mouse Meg3 gene, MEG3 , is found to express in the brain and pituitary (Gejman et al, 2008).…”
Section: Discussionmentioning
confidence: 99%